Synthesis, crystal structure elucidation, Hirshfeld surface analysis, 3D energy frameworks and DFT studies of 2-(4-fluorophenoxy) acetic acid - Prabhuswamy, Akhileshwari; Mohammed, Yasser Hussein Eissa; Al-Ostoot, Fares Hezam; Venkatesh, Geetha Doddanahalli; Anandalwar, Sridhar Mandayam; Khanum, Shaukath Ara; Krishnappagowda, Lokanath Neratur (European Journal of Chemistry, 2021)
The compound 2-(4-fluorophenoxy) acetic acid was synthesized by refluxing, 4-fluoro-phenol as a starting material with ethyl chloroacetate in acetone as solvent. The compound crystallizes in the monoclinic crystal system with the space group P21/c. Crystal data for C8H7FO3, a = 13.3087(17) Å, b = 4.9912(6) Å, c = 11.6018(15) Å, β = 104.171(4)°, V = 747.21(16) Å3, Z = 4, T = 293(2) K, μ(CuKα) = 1.142 mm-1, Dcalc = 1.512 g/cm3, 8759 reflections measured (13.72° ≤ 2Θ ≤ 130.62°), 1246 unique (Rint = 0.0528) which were used in all calculations. The final R1 was 0.0458 (>2sigma(I)) and wR2 was 0.1313 (all data). The structure was stabilized by C-H···O and C-H···Cg interactions. The intermolecular interactions in the crystal were studied using Hirshfeld surface analysis. 3D energy frameworks were computed to visualize the packing modes. DFT calculations were performed. The FMOs were studied to estimate the kinetic stability and reactivity of the molecule. The MEP surface was generated to investigate the charge distribution and chemical reactive sites in the molecule.